USE OF INTERACTIVE METHODS IN DEVELOPING CREATIVITY OF STUDENTS OF HIGHER EDUCATION INSTITUTIONS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The article talks about educational technologies for increasing the creativity and activity of higher education students. In the development of the field of education, it is mentioned about the effectiveness of using interactive educational methods to increase creativity, not to get bored of the student and to strengthen the ability to fully express his opinion. In the course of the lesson, priority ideas such as the organization of various games to increase the student's activity were put forward.